Career Recommendation System for Validation of Multiple Intelligence to High School Students (2021)
Career choice is a critical moment for any student. However, many students worldwide change of path during the first academic year. Vocational tests are tools to help students choose an upper education career by providing information about their abilities and interests. However, some of them are very difficult to apply high costs, availability, or not validated at diverse populations. Gardner’s Multiple Intelligence test is a popular test that measures the brain’s performance abilities in nine areas. Unlike IQ’s test, Gardner Test is helpful to understand students’ strengths and learning styles. Vocational tests and Multiple Intelligence test measure students’ abilities and interests. This research shows the implementation of a recommendation system based on the Gardner test, we considering familiar variables and results of a basic knowledge test. For validation, we compare it with a standard vocational test. Our system recommends a top five of careers with 88.2% success and 93.3% for the top one. © 2021, Springer Nature Switzerland AG.